“Influencia del ácido -3- indol butírico y tipo de sustrato en el enraizamiento de plukenetia huayllabambana en cámaras de sub irrigación en la provincia de San Martín” - Angulo Ríos, Gianfraco (2016)
This research has the specific purpose of determining the highest and best answer rooting Plukenetia huayl/abambana (Bussmann et al., 2009), through four doses of acid indole-3-butyric and two types of substrates cameras sub irrigation in the province of San Martín. This research was conducted at the premises of the Research lnstitute of the Peruvian Amazon llAP - San Martin, located in the district of Morales, province and department of San Martín; UTM coordinates of which they are N 9283654 and 0347742 E and at an altitude of 332 m.s.n.m.m. For the implementation of this research design was completely randomized factorial arrangement 4 x 2 (4 doses of AIB and 2 types of substrate) with 3 replications and 12 cuttings per experimental unit. The results obtained in the field were processed using the statistical program insfostat. Data were analyzed using analysis of variance and subjected to the Tukey test with a significance level (p <0.05) probability of error in determining the nature of the differences between treatments. Previous analysis, data rooting percentage, number of roots, percentage of sprouting, were transformed by arcsin formula and processed data count (Snedecor and Cochran 1980). (Pampa Hermosa) - Stakes kind of Plukenetia huayllabambana (Bussmann. 2009), which were collected in the region of Amazonas province Rodríguez de Mendoza, Limabamba District were used. The variables evaluated were: percentage of rooting, number of roots, root length and percentage of sprouting. The results indicate that the best dose of acid indole-3- butyric rooting juvenile cuttings in Plukenetia huayllabambana, was 0.6% of AIB, compared to other doses of AIB. The type of substrate with the best results was fine for rooting juvenile cuttings in Plukenetia huayllabambana gravel. Keywords: Plukenetia, influence, acid, butyric indole, dosage, substrate, fine gravel, half sand, sprouting, roots, percentage, rooting.